A partially broken Shiva linga - Temples of India Project Team (Jio Institute, 2024)
A partially broken Shiva linga (an iconic representation of Shiva) is found on the eastern side of the Neelkanth Mahadev Temple. This could be the original object of worship in the central shrine of the Neelkanth Mahadev Temple, as the one inside the temple is a new linga.